Comparison between vertical and horizontal drilling of oil and gas well [electronic resource] - Intan Hairunnisa Salleh, 1981- (2010)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Struktur dan Bahan)) - Universiti Teknologi Malaysia, 2010